IMPLEMENTASI DIVERSI GUNA MEWUJUDKAN RESTORATIVE JUSTICE DALAM SISTEM PERADILAN PIDANA ANAK. - Witasari, Aryani; Arif, Muhammad Sholikul (Jurnal Hukum, 2019)
The research objective is to identify and analyze the implementation of Diversion in order to realize Restorative Justice in the Juvenile Criminal Justice System in an effort to provide legal protection for child criminal offenders. The approach method used in this research is normative juridical or library law research or doctrinal law research, namely legal research by examining library materials and secondary materials, the results of the study found that the obligation to seek diversion with the Restorative Justice approach at every stage in the criminal justice process Children must be carried out in the Criminal Justice System, Diversion as a step towards transferring the settlement of children's cases from the criminal justice process to non-criminal justice processes by prioritizing the Restorative Justice approach which can be carried out by way of deliberation or mediation which emphasizes efforts to restore back to its original state in a friendly manner.